PENGARUH CITRA MEREK TERHADAP LOYALITAS NASABAH PADA PT.BRI UNIT BUMI NYIUR - Lestiani, Dewi Indra (Fakultas Ekonomi Universitas Tadulako, 2017)
This study aims to analyze the influence of: (1) brand image, consisting of corporate image, customer image, and product image on customer loyalty at PT. BRI Unit Bumi Nyiur Palu. (2) corporate image on customer loyalty at PT. BRI Unit Bumi Nyiur of Palu. (3) customer image on customer loyalty at PT. BRI Unit Bumi Nyiur of Palu. (4) product image on customer loyalty at PT. BRI Unit Bumi Nyiur of Palu. Type of study is causal descriptive. Population includes customers at PT. BRI Unit Bumi Nyiur of Palu. Sampling technique is purposive sampling, with 100 respondents as samples. Method of analysis is multiple regression analysis. The results show that (1) brand image consisting of corporate image, customer image, and product image simultaneously have significant influence on customer loyalty at PT. BRI Unit Bumi Nyiur of Palu (2) Corporate image has a significant influence on customer loyalty at PT. BRI Unit Bumi Nyiur of Palu, (3) customer image has a significant influence on customer loyalty at PT. BRI Unit Bumi Nyiur of Palu, (4) product image significantly influences customer loyalty at PT. BRI Unit Bumi Nyiur of Palu.